Behavioural Intervention for People Living with HIV/AIDS with Ambivalent Attitudes toward the COVID-19 Vaccine - Schweitzer, Ana-Maria; Melinte-Rizea, Elena; Androne, Alexandra Florentina; Niculaie, Florica; Bagaiof, Cristina; Bogdan, Mihaela; Mihale, Stefania Florentina (Technium Social Sciences Journal, 2022)
The COVID-19 vaccination program was made available in Romania first to vulnerable and at-risk groups in specific state-run centers, where people could get an appointment and receive the shot. People Living with HIV/AIDS (PLWHA) represent such a group. In the context of widespread misinformation and debate about the need for vaccination, our team took a proactive approach to assess vaccination levels and intentions among the unvaccinated. 100 PLWHA who declared ambivalent or unprepared to take the vaccine were offered one online or in-person counseling session. As part of the standard counseling protocol, psychologists asked patients about their intention to get vaccinated on a scale from 1 to 10 at the beginning of the session and again at the end. The protocol imposed that the counselor uses any combination of one or more of the following five behavior change techniques (BCTs): information about social and environmental consequences, credible sources, comparative imagining of future outcomes, anticipated regret, and action planning. Additionally, counselors could use other techniques on an ad-hoc basis if they evaluated this as necessary. Out of the 100 PLWHA at the end of the evaluation, 43 reported they took the vaccine. Sixteen patients in the sample said they took the vaccine by their own decision before the counselor reached out. For the entire group, the intention to get vaccinated increased by 3.36 points (t= -13.25, p< .05). At the follow-up evaluation, there was a 3.16-point increase for the group that did not vaccinate (t= -11.38, p< .05); and 4-point increase for PLWHA who did vaccinate (-6.92, p<.05). Overall, the people in the unvaccinated group started with a significantly lower intention at the beginning of the session than those who eventually got the shot (mean 1.96 versus 3.25). The number of BCTs used was similar in the groups, regardless of vaccination status at the end of the assessment. Our experience shows that an increase in the intention to be vaccinated is possible among ambivalent patients, even when the intervention is limited to one session. The intervention helped approximately 32% of the patients. They were able to act and take the steps necessary to receive the COVID vaccine, while the ones who did not yet act reported a higher intention at the end of the intervention. The baseline intention could indicate the necessary number of follow-up sessions until a successful outcome. Health psychologists must further define the set of BCTs needed for subsequent interventions.